A methodology for electricity option pricing. case of study: colombia (2021)
Electricity is a commodity like no other in the sense that there are no efficient ways of storing it, its transportation is limited by existent electrical networks and its production can be made by different methods. This specific characteristics make electricity prices particularly volatile. Due to this volatility, risk hedging strategies, such as financial options, have been employed. This paper presents a methodology for option pricing with electric energy as underlying asset, taking into account multi-seasonal behavior. Future electricity prices are presented for equatorial countries that have a hydro-dependent electricity production and tropical season (e.g. dry seasons and seasons of wetness) which are mainly affected by the El Ni?no Southern Oscillation (ENSO). Mean reversion processes are used to simulate the hourly spot prices of electric energy, based on the historical prices of the Colombian electricity market. Discussions about the seasonal and climatic effects that affect electricity prices are presented. The results prove that taking into account the effect that the ENSO phenomena make electricity price modeling more accurate. Finally, the Esscher transform is used to price electricity derivatives using the historical electricity prices in the Colombian stock exchange, which are collected by XM.